Blast Hits of Colobanthus quitensis transcriptome - Bertini, Laura; Proietti, Silvia; Caruso, Carla (Dryad Digital Repository, 2015)
All contigs were screened against Viridiplantae protein databases Nr using BLASTx (e-value<10-5) (Altschul et al. 1990).